Intestinal Epithelial Cell–Derived μ-Opioid Signaling Protects against Ischemia Reperfusion Injury through PI3K Signaling - Goldsmith, Jason R. (American Society for Investigative Pathology, 2013)
Intestinal ischemia has a wide variety of causes, including, but not limited to, atherosclerosis, thrombosis, hypotension, and chronic inflammation. In severe cases, ischemic injury can result in death. μ-Opioid receptor (MOR) signaling has previously been shown to protect against chemically induced colitis, but the cellular origin of this effect remains unknown. Herein, we evaluated the role of intestinal epithelial cell (IEC)–derived MOR signaling in host responses to ischemia/reperfusion-induced injury. Ileal ischemia was accomplished through obstruction of the distal branches of the superior mesenteric artery (60 minutes) and reperfusion for 90 minutes (ischemia-reperfusion). Floxed-MOR mice were crossed to Villin-cre transgenic mice to selectively delete the MOR gene in IECs (MOR(IEC−/−)). Radio-ligand binding assays demonstrated selective loss of MOR signaling in IECs of MOR(IEC−/−) mice. The s.c. administration of the MOR agonist, [D-Arg2, Lys4] dermorphin (1–4) amide (DALDA), 10 minutes before surgery protected against both ischemic and reperfusion phases of intestinal injury, an effect abolished in MOR(IEC−/−) mice. This cytoprotective effect was associated with enterocyte-mediated phosphoinositide 3-kinase (PI3K)/glycogen synthase kinase 3β signaling and decreased apoptosis, as determined by IHC and caspase-3 processing. PI3K blockade with Ly294002 resulted in loss of MOR-mediated cytoprotective function. Together, these data show that IEC-derived μ-opioid signaling uses the PI3K pathway to protect cells against the damaging effect of ischemia-reperfusion. Targeting MOR signaling may represent a novel mean to alleviate intestinal injury and promote the wound-healing response.